Ultrasound guided fine needle biopsy of early hepatocellular carcinoma complicating liver cirrhosis: a multicentre study. Issue 9 (11th August 2004) - Caturelli, E; Solmi, L; Anti, M; Fusilli, S; Roselli, P; Andriulli, A; Fornari, F; Del Vecchio Blanco, C; de Sio, I
Abstract : Background: Because hepatic cirrhosis is a major risk factor for hepatocellular carcinoma, recent guidelines by the European Association for the Study of the Liver (EASL) on clinical management of hepatocellular carcinoma recommend periodic ultrasound surveillance of cirrhotic patients with immediate workup for nodules >1 cm; an increase in the frequency of screening is considered sufficient for smaller lesions. Aims: To determine the actual risk of hepatocellular carcinoma associated with the latter lesions and to assess the role of ultrasound guided-fine needle biopsy in their diagnosis Patients and methods: Data were analysed for 294 new nodular lesions <20 mm, including 48 that were <10 mm, detected during a prospective multicentre study involving ultrasound surveillance of 4375 patients with hepatic cirrhosis. In the absence of α fetoprotein (AFP) levels diagnostic of hepatocellular carcinoma, ultrasound guided-fine needle biopsy was performed (n = 274). AFP and fine needle biopsy diagnoses of malignancies (hepatocellular carcinoma and lymphoma) were considered definitive. Non-malignant fine needle biopsy diagnoses (dysplastic or regenerative nodule) were verified by a second imaging study. Diagnoses of hepatocellular carcinoma based on this study were considered definitive; non-malignant imaging diagnoses were considered definitive after at least one year of clinical and ultrasound follow up. Results: Overall, 258/294 (87.6%) nodules proved to be hepatocellular carcinoma, including 33/48 (68.7%) of those ⩽10 mm. Overall typing accuracy of ultrasound guided-fine needle biopsy was 89.4%, and 88.6% for lesions ⩽10 mm. Conclusions: In a screening population, well over half of very small nodules arising in cirrhotic livers may prove to be hepatocellular carcinoma, and approximately 90% of these malignancies can be reliably identified with ultrasound guided-fine needle biopsy.